Preliminary characteristics of laminations in recent sediments from lakes Kamenduł and Perty in the Suwałki Landscape Park, northeastern Poland - Tylmann Wojciech; Kinder Małgorzata; Żarczyński Maurycy; Poraj-Górska Anna (Limnological Review, 2016)
Varved lake sediments are well known archives used for paleoenvironmental reconstructions. They provide continuous, high-resolution and calendar-year chronologies of past environmental changes. From lakes Kamenduł and Perty, located in the Suwałki Landscape Park, short cores of laminated sediments were collected and investigated using microfacies analysis and X-ray fluorescence (XRF) scanning. Sediments of Lake Kamenduł form biogenic (calcite) varves with pale lamina containing precipitated calcite and dark lamina composed of mixed organic and clastic material. There is a visible difference between varves in the lower and the topmost part of the core. The varve thickness and clastic material content decrease upcore. Analysed sediments of Lake Perty also show laminated structures which are biogenic varves composed of calcite laminas interbedded with layers of mixed material and dark laminas containing mostly organic material with some clastic particles. Our study shows that further analysis of sediments from these lakes may provide valuable information about past land use changes in their catchments as well as changes in the water column, i.e. mixing regimes and redox conditions.